Regioselective Green Synthesis and Antimicrobial properties of full fused non mixed Heterocyclic Systems - El-Sayed, Amira A.; El-HAshash, Maher; Rizk, Sameh (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
One pot synthesis and reaction of triazinthione and triazinohydrazide derivatives with different electrophilic reagents in ordered to synthesis of some interesting non-mixed heterocyclic compounds. Structures of thiazolotriazine, triazolotriazine, pyrimidinyltriazine, and triazinotriazine derivatives were established via spectroscopic data and elemental analysis. The synthesized compounds were screened for their antimicrobial activity.